Immigration, prejudice and ethnicity - Cooper, Jeremy (Milton Keynes : The Open University)
Disscusses immigration that came to United States from different part of the world. Also disscusses why they migrate, what happen after they migrate and when they migrate
Copy available in DVD format
Film editor, Doug McLead
Narrator: Stuart Hall
Keywords: Emigration and immigration -- Social aspects; Prejudices; Ethnicity -- United Kingdom